THEORETICAL PRINCIPLES OF THE FORMATION OF THE ECONOMIC STRATEGY OF THE ENTERPRISE IN THE CONTEXT OF STRATEGIC MANAGEMENT - LUKIANOVA, Valentyna; HOLOVACH, Tetiana; ZAKRYZHEVSKA, Iryna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines scientific developments in the field of strategic management. Conscious strategic management allows the management of the enterprise to respond constructively to changes in its economic activity, to identify new opportunities and negative trends; evaluate alternative prospects for development in the future. The classification of scientific schools of strategy formation, which are based on different ideas about the determinants of strategic management, is presented.Each enterprise has its own configuration of initial strategic processes. Scientists have developed a wide range of enterprise management strategies. Enterprise management strategies are characterized by a constant focus on development, the desire to predict the future, and the direction to increase the efficiency of the enterprise. The article justifies the necessity of using a system of strategies. Theoretical approaches to development methodology, formation of a system of strategies for achieving enterprise goals are considered.It has been established that the economic strategy plays the most important role in combining individual elements of the general strategy of the enterprise. It is the main prerequisite for maintaining a high level of efficiency of the enterprise and its competitiveness. The process of forming an economic strategy includes interrelated stages: assessment of the current financial state of the enterprise and existing economic strategy; formation of a set of possible economic strategies; direct selection of an economic strategy using a comparative analysis based on certain principles and criteria. When forming an economic strategy, it is necessary to take into account the organizational and production features of the enterprise, in particular, the industry, goals, potential and resource opportunities, etc. The strategy must be adjusted taking into account the influence of external and internal environmental factors.
Keywords: strategy; strategic management; classification of strategies; system of strategies; formation of strategies; economic strategy